Serum Adiponectin Level and Different Kinds of Cancer: A Review of Recent Evidence. (18th November 2012) - Izadi, Vajihe; Farabad, Elaheh; Azadbakht, Leila
Abstract : Background . Adiponectin, an adipokine secreted from adipose tissue, has antiobesity, anti-insulin resistance, and anticancer roles. The present study aimed to review the epidemiologic evidence about the association between adiponectin and cancers. Method . We searched in PubMed from 2002 to October 2011 by using the following key words: cancer, malignancy, cell proliferation, and adiponectin. Finally, 45 articles were recruited to review in the present paper. Findings . Several findings suggested inverse association between concentration of hormone and breast cancer risk. Low levels of adiponectin increase the risk of endometrial cancer in women. Adiponectin levels were significantly associated with prostate cancer in men. It seems that there is an inverse relationship between levels of adiponectin or its gene and colorectal cancer. Significant association between hormone and pancreatic cancer was found. Conclusion . Several findings suggested the negative correlation between adiponectin and risk of cancers. This relationship was more elucidated by the correlation between the hormone with obesity and insulin resistance. Suppression of growth and proliferation of cancer cells by adiponectin were explained via several mechanisms.